Biocontrol in a warmer world: anticipating the climate suitability of an aggressive invasive plant and its specialist herbivore - Pulzatto, Mikaela Marques; dos Santos Ribas, Luiz Guilherme [UNESP]; de Assis Murillo, Raytha; Florêncio, Fernanda Moreira; Vilà, Montserrat; Thomaz, Sidinei Magela (Springer Nature, 2025)
Climate change may exacerbate alien species expansion into previously unsuitable areas. This shift in species distributions can lead to mismatches between interacting species. We evaluated the potential worldwide distribution of the invasive plant Alternanthera philoxeroides, and its specialist herbivore, the flea beetle Agasicles hygrophila, under future global warming scenarios to identify overlapping and non-overlapping areas. We used species distribution models (SDMs) to predict the potential global distribution of both species in current, and in moderately optimistic and pessimistic scenarios. Climate change is expected to significantly expand A. philoxeroides toward higher latitudes, increasing its global range and climatic suitability. Agasicles hygrophila is also predicted to expand, albeit to a lesser extent, with some loss of currently suitable areas and a decrease in suitability. The overlapping area between their distributions is projected to increase globally, except in the USA. This suggests promising biocontrol potential for alligator weed in many regions in the future, but portions of its distribution may remain unsuitable for the flea beetle, particularly at higher latitudes. The northward expansion of the plant beyond the flea beetle’s range may create zones with low control efficiency. These findings can help management strategies for this invasive plant under its future potential distribution.
Keywords: Agasicles hygrophila; Alligator weed; Althernanthera philoxeroides; Biological control efficiency; Climate change; Flea beetle; Global warming; Species distribution model